Nationwide trends and projections of peripheral arterial disease among Danish adults. (3rd October 2022) - Soegaard, M; Nielsen, P B; Eldrup, N; Behrendt, C A; Lip, G Y H; Larsen, T B; Skjoeth, F
Abstract: Background: Peripheral arterial disease (PAD) is a critical clinical and public health issue with a prevalence of >10% worldwide among adults ≥50 years. Whether this occurrence has been increasing, decreasing or stable over time remains a matter of debate as contemporary population data are sparse and conflicting. Purpose: To quantify changes in PAD incidence, prevalence, and mortality and provide projections for future prevalence development through 2050. Methods: We conducted nationwide analyses of the entire Danish population aged ≥40 years from 2000 through 2018 to assess national trends in diagnosed PAD incidence, prevalence, and all-cause mortality, overall and by sex and age-groups. PAD was identified by primary or secondary in-hospital or outpatient clinic diagnoses, and incident cases comprised individuals whose preceding complete hospital history, potentially back to 1977, lacked a PAD diagnosis. Based on observed trends in incidence and PAD mortality between 2000–2018, and the projected future annual age distribution and population mortality obtained from Statistics Denmark, we projected the future prevalence of PAD through 2050. Results: The population of Denmark aged 40–99 years between 2000 and 2018 included 4, 508, 932 individuals, among whom we identified 123, 479 incident diagnoses of PAD during 51, 4 million person-years of follow-up. The age- and sex-standardized incidence of PAD decreased from 2.70 per 1, 000 person-years in 2000 to 1.79 in 2018 (incidence rate ratio 0.67, 95% confidence interval (CI) 0.65–0.70) (Figure 1). The incidence was approximately 20% higher in men than in women but the accentuation was similarly in both sexes. Concurrently, the overall prevalence of PAD in the Danish adult population increased from 0.8% to 1.7% (prevalence ratio 2.12, 95% CI 2.09–2.15). The prevalence rose considerably in the oldest age groups; in 2018 the prevalence was 5.8% in women and 8.0% in men aged ≥80 years. The age- and sex-standardized annual mortality among patients with PAD decreased from 9.9% in 2000 to 7.0% in 2018, representing a mortality ratio of 0.82 (95% CI 0.75–0.91). Projections of PAD prevalence demonstrated that the rise in the national prevalence of PAD will continue until around 2030 followed by a decline towards 2050 (Figure 2). Among individuals aged ≥80 years, the prevalence was projected to reach a maximum of 8.9% for men vs. 6.5% for women before beginning to decline. Conclusion: Within an unselected nationwide population, the incidence and all-cause mortality of PAD has declined over the last two decades. Concurrently, the prevalence increased, and this increasing trend was projected continue over the coming decade before reaching a breaking point around 2030, underscoring the continued need for health service to manage PAD and its complications in years to come. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Karen Elise Jensen's Foundation